ANALISIS NILAI MARKET JAMINAN PINJAMAN DENGAN METODE MOORA - Gortap Lumbantoruan; Eviyanti Novita Purba (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Credit is the provision of loan money based on an agreement or loan agreement between the creditor and other parties. Credit is made after an agreement is reached between the bank or creditor and the debtor or credit recipient in which there are rights and obligations of each party. Usually banks or financial services are willing to provide loans if the debtor provides his assets as collateral or collateral to ensure the smooth running of his debt. The assessment of the guarantee or collateral must be carried out objectively and apply the precautionary principle. The estimated market value (market value) of the collateral must be based on real market data so as not to harm the creditor. To assist the lender in analyzing the market value of the collateral submitted by the debtor, the author uses the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method by using several criteria including the status of documents/collateral letters, asset allocation, road conditions, locations and several other factors. From the results of the analysis using the MOORA method on the market value of the collateral submitted by the debtor, there is a difference with the market value circulating in the community. The results of this analysis can also be used as a reference in making a decision whether or not the object of the collateral submitted is appropriate to the amount of the loan being submitted. Keywords: Credit, Market Value, Collateral, MOORA.